The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.7326/0003-4819-120-4-199402150-00003
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Nosocomial Clostridium difficile–Associated Diarrhea by Restricting Clindamycin Use

Abstract: A nosocomial epidemic of C. difficile diarrhea was controlled by analysis of antibiotic use patterns and by subsequent restriction of clindamycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(106 citation statements)
references
References 0 publications
3
98
1
3
Order By: Relevance
“…Pepin and colleagues found that older patients with multiple comorbidities were more likely to develop [7] as were patients treated with proton pump inhibitors [28] or tube feedings [29]. Most have described an association between antibiotics, particularly the use of cephalosporins, clindamycin, or fluoroquinolones and CDAD [7,[30][31][32][33][34]. There were large differences in CDAD cases across hospitals, metropolitan statistical areas, and states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pepin and colleagues found that older patients with multiple comorbidities were more likely to develop [7] as were patients treated with proton pump inhibitors [28] or tube feedings [29]. Most have described an association between antibiotics, particularly the use of cephalosporins, clindamycin, or fluoroquinolones and CDAD [7,[30][31][32][33][34]. There were large differences in CDAD cases across hospitals, metropolitan statistical areas, and states.…”
Section: Discussionmentioning
confidence: 99%
“…by reducing normal colonic flora with antibiotics used to treat another infection, followed by patients' inoculation with C. difficile spores [33,34]. Despite the long-held view of CDAD pathophysiology, a recent systematic review investigated the association of antibiotics with CDAD in order to summarize the strength of the evidence for this relationship [37].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that restriction of clindamycin use was associated with a reduction in nosocomial CDAD cases (Brown et al, 1990;Pear et al, 1994). Other hospitals' rates of CDAD decreased, by at least 50 %, after restricting cephalosporin use (Ludlam et al, 1999;Khan & Cheesbrough, 2003).…”
Section: Control Of Cdadmentioning
confidence: 99%
“…Initiate an antimicrobial stewardship program (A-II). 22,[25][26][27]32,54,55 a. Assess the appropriateness of antimicrobial prescribing practices.…”
Section: Place Patients With Diarrhea Under Contact Precautions Whilementioning
confidence: 99%